Age Related Morphological Studies on the Tongue of Non-Descript Sheep of Jammu Region with Special Emphasis on Lingual Papillae - Sethi, Lovish; Sarma, Kamal; Suri, Shalini; Devi, Jonali; Singh Sasan, Jasvinder; Chakraborty, Dibyendu (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The tongue of the non-descript sheep (n = 18) was a spatula shaped mobile organ consisting of apex, body, and root. The apex was notched at the centre. A longitudinal groove on the dorsal surface was present which was more apparent in the adult and senile groups. Caudo-dorsal portion of the body presented torus linguae, in front of which was a transverse fossa linguae. Dorsal surface of the tongue was covered by filiform, fungiform, conical, lenticular, and circumvallate papillae. Filiform papillae were pointed, thread-like, and directed caudally and were most abundant. Fungiform papillae were mushroom-shaped. Filiform and fungiform papillae were also present on the ventral surface of the tongue tip in ‘V’ configuration in all three age groups (below 1 year; 2-3 years,and 4 years and above). Lenticular papillae were found on the torus linguae. Largest lenticular papillae were placed along the midline of the prominence. Conical papillae were found lateral to lenticular papillae and orientated caudally. They were greater in the centre and smaller towards the caudal and lateral aspects. Circumvallate papillae were spherical and encircled by a deep moat which was surrounded by a slightly higher mucosal ring. They were arranged in two rows. Weight and volume of the tongue was significantly (p<0.05) greater in senile group followed by adult and least in the young sheep. In all the three age groups, length of the body was the longest part whereas root was the shortest. Width and thickness of the tongue was maximum at the level of torus linguae in all the age groups. Width of the tongue at apex, body and torus linguae showed significant difference (p<0.05) and thickness at apex and torus linguae showed significant difference (p<0.05). Total numbers of vallate papillae were the highest in senile group but the difference was non-significant among various age groups.